Generating X-ray Reports Using Global Attention - Zeiser, Felipe André; Costa, Cristiano André da; Ramos, Gabriel de Oliveira; Bohn, Henrique C.; Santos, Ismael; Donida, Bruna; Brun, Ana Paula de Oliveira; Zarichta, Nathália (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2022)
The use of images for the diagnosis, treatment, and decision-making in health is frequent. A large part of the radiologist’s work is the interpretation and production of potentially diagnostic reports. However, they are professionals with high workloads doing tasks operator dependent, that is being subject to errors in case of non-ideal conditions. With the COVID-19 pandemic, healthcare systems were overwhelmed, extending to the X-ray analysis process. In this way, the automatic generation of reports can help to reduce the workload of radiologists and define the diagnosis and treatment of patients with suspected COVID-19. In this article, we propose to generate suggestions for chest radiography reports evaluating two architectures based on: (i) Long short-term memory (LSTM), and (ii) LSTM with global attention. The extraction of the most representative features from the X-ray images is performed by an encoder based on a pre-trained DenseNet121 network for the ChestX-ray14 dataset. Experimental results in a private set of 6650 images and reports indicate that the LSTM model with global attention yields the best result, with a BLEU-1 of 0.693, BLEU-2 of 0.496, BLEU-3 of 0.400, and BLEU-4 of 0.345. The quantitative and qualitative results demonstrate that our method can effectively suggest high-quality radiological findings and demonstrate the possibility of using our methodology as a tool to assist radiologists in chest X-ray analysis.